Micropropagation protocol for Stevia rebaudiana through axillary shoot proliferation - SINGH, BALRAM; GAJERA, BHAVESH; DESAI, PARTH; MODI, ARPAN; PATIL, GHANSHYAM; NARAYANAN, SUBHASH (The Indian Journal of Agricultural Sciences, 2020)
The present investigation was carried out at Anand Agricultural University, Gujarat during the year 2016 to develop a micropropagation protocol for mass multiplication of medicinally rich stevia plants. Axenic culture was established by sequential application of 200 mg/l Kanamycin, 200 mg/l Carbendazim-50% and 1000 mg/l HgCl2. Out of two different basal media, viz. Gamborg (B5) and Murashige and Skoog (MS) used, full strength MS gave highest (98%) culture establishment. Out of three different basal media, viz. Gamborg’s (B5), Linsmair and Skoog (LS), Murashige and Skoog (MS) and four different cytokinins, viz. 6-benzylaminopurine (BAP), Kinetin (Kn), Thiadiazuron (TDZ), Zeatin (Zn) tested for multiple shoot induction, full strength MS medium and 2 mg/l BAP, respectively, promoted maximum shoot formation. In the experiment to study the effect of varying strength of MS media and various plant growth regulators, viz. Indole-3-acetic acid (IAA), Indole-3-butyric acid (IBA), Naphthalene acetic acid (NAA) on in vitro rooting, ½ strength MS and 1 mg/l NAA, respectively, gave superior response. Among the 26 different combinations of potting mixtures used for primary acclimatization of in vitro rooted plants, cocopeat based substrates yielded highest survival rate (75.06%). Secondary acclimatization was carried out in the soil bags in the poly house. Thus, a reproducible and reliable micropropagation protocol for mass multiplication of Stevia rebaudiana (Bertoni) Bertoni using nodal segments has been developed.